Effects of Dietary Maltol on Innate Immunity, Gut Health, and Growth Performance of Broiler Chickens Challenged With Eimeria maxima - Park, Inkyung; Goo, Doyun; Nam, Hyoyoun; Wickramasuriya, Samiru S.; Lee, Kichoon; Zimmerman, Noah P.; Smith, Alexandra H.; Rehberger, Thomas G.; Lillehoj, Hyun S. (Frontiers in Veterinary Science, 2021)
Two studies were conducted to evaluate the effects of maltol as a postbiotic on innate immunity, gut health, and enteric infection. In the first study, an in vitro culture system was used to evaluate the effects of maltol on the innate immune response of chicken macrophage cells (CMC), gut integrity of chicken intestinal epithelial cells (IEC), anti-parasitic activity against Eimeria maxima, and differentiation of quail muscle cells (QMC) and primary chicken embryonic muscle cells (PMC). All cells seeded in the 24-well plates were treated with maltol at concentrations of 0.1, 1.0, and 10.0 μg. CMC and IEC were stimulated by lipopolysaccharide to induce an innate immune response, and QMC and PMC were treated with 0.5 and 2% fetal bovine serum, respectively. After 18 h of incubation, pro-inflammatory cytokines, tight junction proteins (TJPs), and muscle cell growth markers were measured. In the second study, the dietary effect of maltol was evaluated on disease parameters in broiler chickens infected with E. maxima. Eighty male 1-day-old broiler chickens were allocated into the following four treatment groups: (1) Control group without infection, (2) Basal diet with E. maxima, (3) High maltol (HI; 10.0 mg /kg feed) with E. maxima, and (4) Low maltol (LO; 1.0 mg/kg feed) with E. maxima. Body weights (BW) were measured on days 0, 7, 14, 20, and 22. All chickens except the CON group were orally infected with 104E. maxima per chicken on day 14. Jejunum samples were collected for gut lesion scoring, and the gene expression of cytokines and TJPs. Data was analyzed using PROC MIXED in SAS. In vitro, maltol not only increased TJPs in IEC and cytokines in the LPS-stimulated CMC but also showed direct cytotoxicity against sporozoites of E. maxima. In vivo, the HI group improved the BW, reduced the gut lesion scores and fecal oocyst shedding, and decreased jejunal TNFSF15 and IL-1β expression in E. maxima-infected chickens. In conclusion, these results demonstrate the beneficial effects of dietary maltol in the enhancement of growth performance, gut health, and coccidiosis resistance and the applicability of maltol as a postbiotic for the replacement of antibiotic growth promoters in commercial poultry production.